The Effects of a Delirium Management Application on Critical Care Nurses' Knowledge and Clinical Judgment: A Quasi-Experimental Study - Meenongwah, Jaroonsree; Promwong, Waiyaporn; Sirirungsankul, Pensri; Ngarmnet, Thatdao; Phorart, Sasithorn; Yusuk, Sasinaphon; Nilas, Jantana; Reangsan, Deanram; Srakaew, Warisara; Suwannakhet, Rujitrada; Pratumwong, Laddawun; Namuangrak, Vanarat (National Journal of Community Medicine, 2026)
Background: Delirium is a critical condition in critically ill patients. It affects mechanically ventilated patients and leads to increased mortality, prolonged hospitalization, and high healthcare costs. This study aimed to investigate the impact of a delirium management application on nurses' knowledge and clinical judgment in the context of delirium care. Methodology: A quasi-experimental design was employed over three weeks in a tertiary hospital in Thailand. Twenty-three critical care nurses were recruited using a consecutive sampling method. Data were collected using delirium knowledge and clinical judgment assessment questionnaires. The Wilcoxon Signed-Rank test was used to compare the pre- and post-test scores. Results: Twenty-three participants were included. The median post-test scores for knowledge and clinical judgment were 47.00 (Interquartile range: IQR 46.00-52.00) and 11.00 (9.00-15.00), respectively, compared to mean pre-test scores of 44.00 (IQR 42.00-45.00) and 8.00 (IQR 7.00-9.00), indicating a significant difference in these outcomes after using the application (z -3.884 and -3.485, p <0.001). Conclusion: The delirium management application was associated with improvements in critical care nurses’ knowledge and clinical judgment regarding delirium management. These preliminary findings suggest that the application may have potential as a supportive digital tool for addressing knowledge and practice gaps in delirium management in the intensive care unit.